Preparation method of carbon-modified zinc-doped titanium dioxide nanofiber sheet photocatalyst

By decorating carbon particles and doping zinc on titanium dioxide nanofibers to form small photocatalysts of carbon-modified zinc-doped titanium dioxide nanofibers, the existing photocatalysts have been solved, and efficient water pollution removal and material recovery have been achieved.

CN116173937BActive Publication Date: 2025-03-25JIAMUSI UNIVERSITY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310221407.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-02
Publication Date
2025-03-25
Estimated Expiration
2043-03-02

AI Technical Summary

Technical Problem

The existing nanoscale titanium dioxide photocatalysts have shortcomings in structure and morphological design, resulting in low photocatalytic efficiency and the nanoparticles are prone to agglomeration and difficulty in recycling.

Method used

By decorating carbon particles on titanium dioxide nanofibers, a small photocatalyst of carbon modified zinc-doped titanium dioxide nanofibers is formed, and zinc and carbon atoms are used to enter the titanium dioxide lattice, increasing crystal defects and oxygen vacancies, and improving light absorption and carrier mobility.

Benefits of technology

The photocatalytic efficiency of the photocatalyst is improved, the light absorption rate and carrier mobility are enhanced, and the problem of difficulty in agglomeration and recycling of nanoparticles is solved, achieving efficient water pollution removal.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116173937B_ABST
    Figure CN116173937B_ABST
Patent Text Reader

Abstract

The present invention provides a method for preparing a carbon-modified zinc-doped titanium dioxide nanofiber flake photocatalyst, comprising: drying zinc acetate dihydrate to remove crystal water, dissolving butyl titanate and zinc acetate in anhydrous ethanol and glacial acetic acid solvents, adding polyvinyl pyrrolidone, and generating a light yellow transparent sol at room temperature; electrostatically spinning the obtained sol, calcining the nanofiber membrane in air, and then naturally cooling to room temperature; dispersing the calcined nanofiber flakes into anhydrous ethanol and deionized water solution, adding dimethylformamide and glacial acetic acid for hydrothermal reaction, calcining and carbonizing in a protective gas, and obtaining a carbon-modified zinc-doped titanium dioxide nanofiber flake photocatalyst. The present invention improves the photocatalytic efficiency of anatase titanium dioxide through zinc doping and carbon modification, and at the same time, the nanofiber flakes have a large deposition rate and are easy to precipitate and recover, solving the problem of easy agglomeration and difficulty in recovery of nanoparticles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a nanofiber sheet photocatalyst, in particular to a method for preparing a carbon-modified zinc-doped titanium dioxide nanofiber sheet photocatalyst. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] With the increasing concern about environmental pollution, water pollution has become an environmental problem that needs to be solved urgently. Therefore, efficient and sustainable technologies are urgently needed to reduce the content of pollutants in wastewater. Organic dyes are one of the main pollutants in industrial wastewater such as printing and dyeing, plastics, and chemicals. The residual dyes in wastewater are harmful to animals, plants, and humans due to their non-degradability and toxicity. Compared with bulk materials and large particle materials, nanomaterials have a larger exposure area and can provide more catalytic active sites for redox reactions, which is the key to the adsorption and activation of reactant molecules. Nanoscale photocatalytic materials have been widely used in various pollutant removal and material self-cleaning due to their unique physical and chemical properties such as large specific surface area, good adsorption, and high catalytic efficiency. Titanium dioxide has become an attractive photocatalytic semiconductor due to its good thermal and chemical stability, low cost, and environmental friendliness. Titanium dioxide has three crystal structures: anatase, rutile, and brookite. Among them, anatase has the best photocatalytic effect, but anatase has poor stability and is very easy to convert into rutile. At present, there are commercial nano-scale titanium dioxide products, the most common of which is titanium dioxide P25 nano-scale powder, which is a mixture of anatase and rutile with an average particle size of 25 nanometers. There are three deficiencies in the existing products that need to be improved: First, the proportion of anatase phase of titanium dioxide is not high. In order to obtain a higher proportion of anatase titanium dioxide, many methods are used, such as designing different types of chemical reactions, doping without affecting the photocatalytic effect, changing the preparation process and reaction conditions, etc.; Second, even good anatase titanium dioxide itself has structural defects. Titanium dioxide has high photogenerated carrier recombination rate, low mobility, low light absorption rate and other deficiencies, resulting in low photocatalytic efficiency; Third, nano-scale titanium dioxide powder has a small particle size, resulting in a low deposition rate and a long precipitation time. It is difficult to recycle in the treatment of water pollution, and it is easy to form agglomerations in water, affecting the photocatalytic efficiency. In summary, the structural and morphological design of photocatalysts is one of the important methods to improve the photocatalytic efficiency. Summary of the invention

[0004] In view of the deficiencies of the prior art, the present invention provides a method for preparing a carbon-modified zinc-doped titanium dioxide nanofiber flake photocatalyst. The nanoscale photocatalyst is decorated with carbon particles on zinc-doped titanium dioxide anatase nanofibers. The carbon is embedded in the surface of the titanium dioxide fiber in the form of small particles, without wrapping the titanium dioxide fiber, and the carbon exists in the form of graphite. Titanium dioxide, zinc oxide and carbon form multiple heterojunctions. At the same time, zinc and carbon atoms enter the titanium dioxide lattice, increasing lattice defects. Under these two effects, the recombination of photogenerated electrons is suppressed, the mobility of photogenerated carriers is improved, the light absorption rate is enhanced, and the photocatalytic efficiency is improved. The composite material is anatase titanium dioxide, which is a nanofiber flake in morphology, has a large deposition rate, a fast sedimentation rate, and is conducive to recovery in water, solving the above problems.

[0005] To achieve the above objectives, the present invention is implemented through the following technical solutions:

[0006] The preparation method of carbon-modified zinc-doped titanium dioxide nanofiber flake photocatalyst comprises the following steps:

[0007] a. Zinc acetate dihydrate is dried at 100°C to remove crystal water and become zinc acetate. Butyl titanate and zinc acetate are dissolved in anhydrous ethanol and glacial acetic acid solvents. After stirring evenly, polyvinyl pyrrolidone is added and stirred for 5 hours to generate a light yellow transparent sol precursor at room temperature;

[0008] b. electrospinning the obtained sol precursor to form a nanofiber membrane, calcining the nanofiber membrane in air to 400-500° C. to remove polyvinyl pyrrolidone, breaking the large nanofiber membrane into small nanofiber pieces, and then cooling naturally to room temperature;

[0009] c. The calcined nanofiber flakes were dispersed in anhydrous ethanol and deionized water solution, dimethylformamide and glacial acetic acid were added for hydrothermal reaction for 24 hours, the nanofiber flakes were washed with deionized water after hydrothermal reaction, and the nanofiber flakes were calcined and carbonized into graphite in a protective gas at 400°C to obtain carbon-modified zinc-doped titanium dioxide nanofiber flake photocatalysts.

[0010] Preferably, in step a, the mass ratio of butyl titanate and zinc acetate in the sol precursor solution is 100:(2-6).

[0011] Preferably, in step a, the volume ratio of anhydrous ethanol to glacial acetic acid solvent in the sol precursor solution is 10:(0.8-1.2).

[0012] Preferably, the electrospinning voltage in step b is 10 to 30 kV.

[0013] Preferably, in step b, the heating rate for calcining the nanofiber membrane in air is 15-25° C. / hour.

[0014] Preferably, in the hydrothermal reaction solution of step c, the volume ratio of anhydrous ethanol to deionized water is 1:(1.5-2.5), the volume ratio of the mass of the nanofiber flakes to dimethylformamide is 1 g:(80-100 ml), and the volume ratio of dimethylformamide to glacial acetic acid is 5:(0.5-1.5).

[0015] Preferably, the hydrothermal reaction temperature in step c is 100-200°C.

[0016] Preferably, in step c, the carbonization is carried out in a protective gas at 400° C. to obtain graphite to obtain a carbon-modified zinc-doped titanium dioxide nanofiber flake photocatalyst. The protective gas may be nitrogen, an inert gas or any gas that does not chemically react with carbon.

[0017] The invention discloses a method for preparing a carbon-modified zinc-doped titanium dioxide nanofiber flake photocatalyst, wherein the photocatalyst is added to water or wastewater containing organic pollutants to be treated, and then the water or wastewater is subjected to light treatment.

[0018] Beneficial effects of the present invention:

[0019] 1. A method for preparing carbon-modified zinc-doped titanium dioxide nanofiber sheet photocatalyst, which has a simple preparation method, low cost and low equipment requirements.

[0020] 2. The titanium dioxide formed by the present invention is a single anatase crystal with the best photocatalytic effect. Zinc oxide crystals are formed by zinc doping. At the same time, zinc also enters the crystal lattice, which changes the titanium dioxide lattice structure and creates oxygen vacancies. Such oxygen vacancies provide a pathway for the transmission and transfer of photogenerated electron pairs, while also forming more crystal defects, which help prevent the recombination of photogenerated carriers. Carbon modification changes the surface state of titanium dioxide nanofibers, provides more reaction sites, and improves the surface conductivity of titanium dioxide. Carbon modification and zinc doping form multiple semiconductor heterojunctions, which are beneficial to the transmission and transfer of photogenerated electrons. These factors work together to improve the photocatalytic efficiency of titanium dioxide.

[0021] 3. Compared with bulk materials, the nanofiber flakes formed by titanium dioxide nanofibers have nanomaterial characteristics such as large specific surface area and strong adsorption, and high photocatalytic efficiency. At the same time, the nanofiber flakes have a large deposition rate and are easy to precipitate and recover, which solves the problem of easy agglomeration and difficult recovery of nanoparticles. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0023] Attached Figure 1is a Raman spectrum of the nanofiber sheet photocatalyst provided in the embodiments and comparative examples of the present invention;

[0024] Attached Figure 2 is an X-ray diffraction spectrum of the nanofiber flake photocatalyst provided in the embodiments and comparative examples of the present invention;

[0025] Attached Figure 3 is a scanning electron microscope image of the nanofiber sheet photocatalyst provided in the embodiments and comparative examples of the present invention;

[0026] Attached Figure 4 is an X-ray spectrum analysis diagram of the nanofiber sheet photocatalyst provided in an embodiment of the present invention;

[0027] Attached Figure 5 It is a high-resolution transmission electron microscopy image of the nanofiber sheet photocatalyst provided in the embodiment of the present invention.

[0028] Attached Figure 6 It is the fluorescence spectrum diagram of the nanofiber sheet photocatalyst provided in the examples and comparative examples of the present invention. DETAILED DESCRIPTION

[0029] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0030] The invention provides a method for preparing a carbon-modified zinc-doped titanium dioxide nanofiber flake photocatalyst, comprising zinc doped in the titanium dioxide nanofiber and carbon modified on the surface of the titanium dioxide nanofiber, wherein the crystal structure of the titanium dioxide nanofiber is anatase.

[0031] In the present invention, zinc is evenly distributed in titanium dioxide nanofibers, and carbon is evenly modified on the surface of titanium dioxide fibers. The composite structure changes the titanium dioxide anatase crystal structure, provides more oxygen vacancies, increases crystal defects, increases surface reaction active sites, and simultaneously forms multiple heterojunctions, providing more photogenerated electron transmission and transfer channels, thereby improving the photocatalytic efficiency.

[0032] In order to further understand the content, features and advantages of the present invention, the following examples and comparative examples are provided to further illustrate the present invention.

[0033] Example

[0034] The present invention provides a method for preparing a carbon-modified zinc-doped titanium dioxide nanofiber sheet photocatalyst, comprising the following steps:

[0035] a. Zinc acetate dihydrate is dried at 100°C to remove crystal water and become zinc acetate. Butyl titanate and zinc acetate are dissolved in anhydrous ethanol and glacial acetic acid solvents. After stirring evenly, polyvinyl pyrrolidone is added and stirred for 5 hours to generate a light yellow transparent sol precursor at room temperature;

[0036] According to some preferred embodiments, 40 ml of anhydrous ethanol and 4 ml of glacial acetic acid are taken as solvents, 0.16 g of zinc acetate and 4 ml of butyl titanate are added, and after stirring evenly, 3.2 g of polyvinyl pyrrolidone is added and stirred for 5 hours to generate a light yellow transparent sol precursor at room temperature.

[0037] b. electrospinning the obtained sol precursor to form a nanofiber membrane, calcining the nanofiber membrane in air to 400-500° C. to remove polyvinyl pyrrolidone, breaking the large nanofiber membrane into small nanofiber pieces, and then cooling naturally to room temperature;

[0038] According to some preferred embodiments, in order to prevent clogging, electrospinning uses a plastic large-diameter spinning nozzle, the distance between the nozzle and the receiver is 10 cm, the positive spinning voltage is 10 kV, the negative spinning voltage is negative 10 kV, and the formed nanofilm is calcined to 500°C in air, with a heating rate of 25°C / hour.

[0039] c. The calcined nanofiber flakes were dispersed in anhydrous ethanol and deionized water solution, dimethylformamide and glacial acetic acid were added for hydrothermal reaction for 24 hours, the nanofiber flakes were washed with deionized water after hydrothermal reaction, and the nanofiber flakes were calcined and carbonized into graphite in a protective gas at 400°C to obtain carbon-modified zinc-doped titanium dioxide nanofiber flake photocatalysts.

[0040] According to some preferred embodiments, 0.1 g of calcined nanofiber flakes are dispersed in a solution of anhydrous ethanol and deionized water in a volume ratio of 1:2, 10 ml of dimethylformamide and 2 ml of glacial acetic acid are added to carry out hydrothermal reaction at 180°C for 24 hours, washed with deionized water 6 times after hydrothermal reaction, and calcined in nitrogen at 400°C for 1 hour for carbonization.

[0041] Comparative Example 1

[0042] a. Butyl titanate is dissolved in anhydrous ethanol and glacial acetic acid solvent, stirred evenly, and then polyvinyl pyrrolidone is added and stirred for 5 hours to generate a light yellow transparent sol precursor at room temperature;

[0043] According to some preferred embodiments, 40 ml of anhydrous ethanol and 4 ml of glacial acetic acid are taken as solvents, 4 ml of butyl titanate is added, and after stirring evenly, 3.2 g of polyvinyl pyrrolidone is added and stirred for 5 hours to generate a light yellow transparent sol precursor at room temperature.

[0044] b. electrospinning the obtained sol precursor to form a nanofiber membrane, calcining the nanofiber membrane in air to 400-500° C. to remove polyvinyl pyrrolidone, breaking the large nanofiber membrane into small nanofiber pieces, and then cooling naturally to room temperature;

[0045] According to some preferred embodiments, in order to prevent clogging, electrospinning uses a plastic large-diameter spinning nozzle, the distance between the nozzle and the receiver is 10 cm, the positive spinning voltage is 10 kV, the negative spinning voltage is negative 10 kV, and the formed nanofilm is calcined to 500°C in air, with a heating rate of 25°C / hour.

[0046] c. The calcined nanofiber flakes were dispersed in anhydrous ethanol and deionized water solution, dimethylformamide and glacial acetic acid were added for hydrothermal reaction for 24 hours, the nanofiber flakes were washed with deionized water after hydrothermal reaction, and the nanofiber flakes were calcined and carbonized into graphite in a protective gas at 400°C to obtain carbon-modified zinc-doped titanium dioxide nanofiber flake photocatalysts.

[0047] According to some preferred embodiments, 0.1 g of calcined nanofiber flakes are dispersed in a solution of anhydrous ethanol and deionized water in a volume ratio of 1:2, 10 ml of dimethylformamide and 2 ml of glacial acetic acid are added to carry out hydrothermal reaction at 180°C for 24 hours, washed with deionized water 6 times after hydrothermal reaction, and calcined in nitrogen at 400°C for 1 hour for carbonization.

[0048] Comparative Example 2

[0049] a. Zinc acetate dihydrate is dried at 100°C to remove crystal water and become zinc acetate. Butyl titanate and zinc acetate are dissolved in anhydrous ethanol and glacial acetic acid solvents. After stirring evenly, polyvinyl pyrrolidone is added and stirred for 5 hours to generate a light yellow transparent sol precursor at room temperature;

[0050] According to some preferred embodiments, 40 ml of anhydrous ethanol and 4 ml of glacial acetic acid are taken as solvents, 0.16 g of zinc acetate and 4 ml of butyl titanate are added, and after stirring evenly, 3.2 g of polyvinyl pyrrolidone is added and stirred for 5 hours to generate a light yellow transparent sol precursor at room temperature.

[0051] b. electrospinning the obtained sol precursor to form a nanofiber membrane, calcining the nanofiber membrane in air to 400-500° C. to remove polyvinyl pyrrolidone, breaking the large nanofiber membrane into small nanofiber pieces, and then cooling naturally to room temperature;

[0052] According to some preferred embodiments, in order to prevent clogging, electrospinning uses a plastic large-diameter spinning nozzle, the distance between the nozzle and the receiver is 10 cm, the positive spinning voltage is 10 kV, the negative spinning voltage is negative 10 kV, and the formed nanofilm is calcined to 500°C in air, with a heating rate of 25°C / hour.

[0053] Comparative Example 3

[0054] a. Butyl titanate is dissolved in anhydrous ethanol and glacial acetic acid solvent, stirred evenly, and then polyvinyl pyrrolidone is added and stirred for 5 hours to generate a light yellow transparent sol precursor at room temperature;

[0055] According to some preferred embodiments, 40 ml of anhydrous ethanol and 4 ml of glacial acetic acid are taken as solvents, 4 ml of butyl titanate is added, and after stirring evenly, 3.2 g of polyvinyl pyrrolidone is added and stirred for 5 hours to generate a light yellow transparent sol precursor at room temperature.

[0056] b. electrospinning the obtained sol precursor to form a nanofiber membrane, calcining the nanofiber membrane in air to 400-500° C. to remove polyvinyl pyrrolidone, breaking the large nanofiber membrane into small nanofiber pieces, and then cooling naturally to room temperature;

[0057] According to some preferred embodiments, in order to prevent clogging, electrospinning uses a plastic large-diameter spinning nozzle, the distance between the nozzle and the receiver is 10 cm, the positive spinning voltage is 10 kV, the negative spinning voltage is negative 10 kV, and the formed nanofilm is calcined to 500°C in air, with a heating rate of 25°C / hour.

[0058] Characterization and evaluation of nanofiber sheet photocatalysts:

[0059] The nanofiber sheet photocatalysts prepared in the above examples and comparative examples were subjected to Raman spectroscopy, X-ray diffraction, scanning electron microscopy, X-ray energy spectrum analysis, high-resolution transmission electron microscopy, fluorescence spectroscopy characterization and photocatalytic performance testing.

[0060] Figure 1 1 is the Raman spectra of the embodiment, comparative example 1, comparative example 2, and comparative example 3. In the embodiment and comparative example 1, the G band formed by graphite can be seen at 1599, indicating that this method can effectively load carbon on the titanium dioxide nanofibers and exist in the form of graphite. At the same time, it is found that the peak at 507 is reduced, indicating that carbon entering the lattice affects the Raman vibration and weakens the vibration. In the enlarged figure, it can be seen that the peak width of the embodiment and comparative example 1 has changed significantly, and the position of the peak has moved, which also proves that carbon enters the lattice, causing the Raman vibration of the chemical bond to change.

[0061] Figure 2It is the X-ray diffraction pattern of Example, Comparative Example 1, Comparative Example 2 and Comparative Example 3. It can be seen that Example, Comparative Example 1, Comparative Example 2 and Comparative Example 3 are all good titanium dioxide anatase crystals. At the same time, zinc oxide peaks with lower peak values ​​are observed at 31.1° and 36.3° in Example and Comparative Example 2, indicating that zinc partially becomes zinc oxide after doping, but the peak value is not high due to the low content. At the same time, in the magnified view of the highest peak, it can be seen that zinc enters the titanium dioxide lattice, resulting in the movement of the peak position of Example and Comparative Example 2. The widening of the peak width indicates that more crystal defects have appeared in the crystal.

[0062] Figure 3 This is a scanning electron microscope image of the embodiment and comparative example 2. It can be seen that the photocatalyst is composed of nanofibers. Before carbon is added, the fiber surface is smooth. After carbon is added, it can be seen that the carbon is effectively fixed on the fiber surface to form a heterojunction. Due to the good conductivity of carbon, the conductivity of the titanium dioxide fiber surface is increased, which can help electron transfer and transmission.

[0063] Figure 4 It is an X-ray energy spectrum analysis diagram of the embodiment, which illustrates the composition of the elements in the embodiment and gives the proportions of surface titanium, oxygen, zinc and carbon.

[0064] Figure 5 It is a high-resolution transmission electron microscope image of the embodiment, which proves the existence of titanium dioxide and zinc oxide crystals, indicating that the two are in close contact to form a semiconductor heterojunction.

[0065] Figure 6 It is the fluorescence spectra of Example, Comparative Example 1, Comparative Example 2 and Comparative Example 3, which indicates that carbon and zinc have entered the titanium dioxide lattice, affecting the luminescence behavior of titanium dioxide, and the luminescence intensity of Comparative Example 1, Comparative Example 2 and Comparative Example 3 are all lower than that of Example, indicating that they have a higher charge separation rate and a lower charge recombination rate.

[0066] The simulated pollutants used in the photocatalytic test are organic dyes methylene blue, methyl orange, rhodamine B and malachite green, and a xenon lamp is used as a simulated solar light source. The photocatalytic test shows that the photocatalyst prepared in the embodiment has a significantly higher photocatalytic efficiency for the four simulated pollutants than the pure titanium dioxide photocatalyst, as shown in Table 1. This indicates that the carbon-modified zinc-doped high-purity anatase titanium dioxide nanofiber flakes obtained by the method improve the photocatalytic efficiency of the titanium dioxide nanofiber flakes.

[0067] Table 1 Comparison results of photocatalytic test

[0068]

[0069]

[0070] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a carbon-modified zinc-doped titanium dioxide nanofiber sheet photocatalyst, characterized in that: The steps include: a. Zinc acetate dihydrate is dried at 100°C to remove crystal water and become zinc acetate. Butyl titanate and zinc acetate are dissolved in anhydrous ethanol and glacial acetic acid solvents. After stirring evenly, polyvinyl pyrrolidone is added and stirred for 5 hours to generate a light yellow transparent sol precursor at room temperature; b. electrospinning the obtained sol precursor to form a nanofiber membrane, calcining the nanofiber membrane in air to 400-500° C. to remove polyvinyl pyrrolidone, breaking the large nanofiber membrane into small nanofiber pieces, and then cooling naturally to room temperature; c. The calcined nanofiber flakes were dispersed in anhydrous ethanol and deionized water solution, dimethylformamide and glacial acetic acid were added for hydrothermal reaction for 24 hours, the nanofiber flakes were washed with deionized water after hydrothermal reaction, and the nanofiber flakes were calcined and carbonized into graphite in a protective gas at 400°C to obtain carbon-modified zinc-doped titanium dioxide nanofiber flake photocatalysts.

2. The method for preparing the carbon-modified zinc-doped titanium dioxide nanofiber sheet photocatalyst according to claim 1, characterized in that: In the step a, the mass ratio of butyl titanate and zinc acetate in the sol precursor solution is 100:(2-6).

3. The method for preparing the carbon-modified zinc-doped titanium dioxide nanofiber sheet photocatalyst according to claim 1, characterized in that: In the step a, the volume ratio of anhydrous ethanol to glacial acetic acid solvent in the sol precursor solution is 10:(0.8-1.2).

4. The method for preparing the carbon-modified zinc-doped titanium dioxide nanofiber sheet photocatalyst according to claim 1, characterized in that: The electrospinning voltage in step b is 10 to 30 kV.

5. The method for preparing the carbon-modified zinc-doped titanium dioxide nanofiber sheet photocatalyst according to claim 1, characterized in that: In the step b, the heating rate for calcining the nanofiber membrane in air is 15-25° C. / hour.

6. The method for preparing the carbon-modified zinc-doped titanium dioxide nanofiber sheet photocatalyst according to claim 1, characterized in that: In the step c, the volume ratio of anhydrous ethanol to deionized water in the hydrothermal reaction solution is 1:(1.5-2.5), the volume ratio of the mass of the nanofiber pieces to dimethylformamide is 1 g:(80-100 ml), and the volume ratio of dimethylformamide to glacial acetic acid is 5:(0.5-1.5).

7. The method for preparing the carbon-modified zinc-doped titanium dioxide nanofiber sheet photocatalyst according to claim 1, characterized in that: The hydrothermal reaction temperature in step c is 100-200°C.

8. The method for preparing the carbon-modified zinc-doped titanium dioxide nanofiber sheet photocatalyst according to claim 1, characterized in that: In the step c, the carbonization is carried out in a protective gas at 400° C. to obtain graphite, thereby obtaining a carbon-modified zinc-doped titanium dioxide nanofiber flake photocatalyst. The protective gas is nitrogen, an inert gas or any gas that does not chemically react with carbon.

Citation Information

Patent Citations

  • Carbon spot / two-dimensional MoS2 composite photocatalyst and preparation method thereof

    CN108786857A